Pressure Drop in a Metal Foam Centrifugal Breather: A Simulation Approach - Lifen Zhang; Xin Ge; Xinglong Hu; Yaguo Lyu (Aerospace)
One of the main issues faced in the operation of a metal foam centrifugal breather is the high pressure drop. This study investigates the pressure drop of a metal foam centrifugal breather. The numerical simulation research method is adopted. The DPM model is used to calculate the two-phase flow field of the metal foam breather, and the porous medium model is used to replace the metal foam at the breather. The resistance caused by the metal foam is replaced by a distributed resistance added to the fluid. The effects of flow rate, rotational speed, porosity, PPI (pores per inch), and temperature on the pressure drop of the breather are analyzed. The results indicate that rotational speed, flow rate, porosity, and PPI significantly influence the resistance of the metal foam centrifugal breather. The resistance of the breather is directly proportional to the rotational speed, flow rate, temperature, and metal foam pore density, and inversely proportional to the porosity. Temperature has a minor impact on the resistance of the metal foam centrifugal breather. Therefore, the metal foam centrifugal breather is more suitable for low-speed operating conditions.